UJI EFEKANTIINFLAMASI EKSTRAKETANOL BUNGA ROSELA(HIBISCUS sabdariffa Linn.)PADA TIKUS PUTIH JANTAN (Rattus norvegicus) - Abdulkadir , Widy Susanti; Polontalo, Febriyanti (Jurnal Health and Sport, 2011)
An antiinflamatory effect test ofroselaflowers (hibiscus sabdwiffa Linn.) on male rats (Rattus norvegicus)had been carried out. The aim ofthis research is to assay anti-inflamatory effect of rosela extract flowers based on the reduction volume of legs edema inmale rats which induced with albumin 15 male rats divided into 5 groups and each group consisted of 3 rats. control group was given Na-CMC 1% w/v, 2nd ,3\'d and 4 groups were given rosela extract. flowers each 2,5% w/v, 5% w/v and 7,5% respsctively and 5th group was given natrium diclofenac suspension as psitive control. All treatment were given orally with dosage 5 mL/400g body weight. Legs of male rats was signed and measured as first volume using platysmometer, one hour later 0,2 mL albumin sohrtion 1% v/v wasinjected by intraplantary into legs of male rats to induce inflammation and measured as edema volume.Measurement of legs volume was conduct 3 hours with interval 30 minutes. The resrlts showed that all the concentration ofrosella extract flowers were reduced the edema volum, the effect ofreduction edema volume rosela extract flowers 7,5% w/v better than the effect of diclofenac suspension statifically.